2022
DOI: 10.1136/bmjopen-2022-062567
|View full text |Cite
|
Sign up to set email alerts
|

Seropositivity of SARS-CoV-2 in an unvaccinated cohort in British Columbia, Canada: a cross-sectional survey with dried blood spot samples

Abstract: ObjectivesGathering population-based data on prevalence of SARS-CoV-2 infection is vital to the public health response and planning. Current seroprevalence data in BC are limited with respect to considerations of how socioeconomic and demographic factors, such as age, sex, gender, income, identifying as a visibility minority and occupation, are related to SARS-CoV-2 antibody detection due to infection-acquired immunity. We aimed to estimate the SARS-CoV-2 seropositivity in a cohort of British Columbians, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…It is possible that the mechanism behind stress and menstrual changes also involves glucocorticoid receptors in the endometrium 48 . Although SARS-CoV-2 infection and vaccines use can also disrupt reproductive cycles in the short term 7,10 , we do not believe this influenced our findings because we found that the seroprevalence of previous infection in this cohort was 2.9% 49 and vaccines were not widely available to the general BC population at the time of this survey. There are limitations to our study.…”
Section: Discussionmentioning
confidence: 77%
“…It is possible that the mechanism behind stress and menstrual changes also involves glucocorticoid receptors in the endometrium 48 . Although SARS-CoV-2 infection and vaccines use can also disrupt reproductive cycles in the short term 7,10 , we do not believe this influenced our findings because we found that the seroprevalence of previous infection in this cohort was 2.9% 49 and vaccines were not widely available to the general BC population at the time of this survey. There are limitations to our study.…”
Section: Discussionmentioning
confidence: 77%
“…36,39 Still, the available commercial assays do not include DBS as an approved sample type and there is limited real-world comparative performance evidence. 40,41 This study aims to improve our understanding of SARS-CoV-2 seroprevalence in Sub-Saharan Africa…”
Section: Introductionmentioning
confidence: 99%
“…DBS have proven useful for the serological study of different viral infections (HIV, HCV, HBV) in these regions 32,33 and since the start of the pandemic researchers have confirmed DBS are comparable to serum samples 34–38 and present good performance on various commercial platforms 36,39 . Still, the available commercial assays do not include DBS as an approved sample type and there is limited real‐world comparative performance evidence 40,41 …”
Section: Introductionmentioning
confidence: 99%